The Analysis of William Federer’s Viewpoint about the Sources of the Quran - mohsen nouraei; Seyed Kamel Askari; mohamad sharifi (پژوهش نامه معارف قرآنی, 2017)
Quranic research has been a top priority for the Orientalists in recent centuries. Some of these works affirm the denial or, at least, skepticism in the Quranic revelation. William Joseph Federer, the contemporary American author and historian, also agrees with this view, denies the divinity of the Quran. The present study, using a descriptive-analytic method, discusses the various aspects of Federer’s claim. This study examines William Federer’s view in his book entitled “What every American needs to know about the Quran” discussing the sources of Quran. The result of the present study shows the inaccuracy of many of Federer’s claims. His most important weaknesses are having no reference to first-hand and authoritative sources, inaccurate addressing to sources, having no reference to Shia’s historical, exegetical and hadith sources, the bias towards Christian beliefs, and prejudice against the Quranic teachings. The result of this research has implications for orientalism studies, and also for theological and exegetical discussions. These results are also effective in the field of advertising and attracting non-Muslims and satisfying their intellectuals.